PENANAMAN NILAI-NILAI KEBANGSAAN PADA SISWA SEKOLAH DASAR DI TAPANULI SELATAN - SIREGAR, ERWIN (JURNAL EDUCATION AND DEVELOPMENT, 2016)
Nationalism is a belief held by most people in which they expressed a sense of nationhood as a feeling of belonging together within a nation. In the practice of everyday life of the students in the southern Tapanuli has not been able to demonstrate the values ââof nationalism. Strengthening the sense of nationhood on the whole nation to be touching sense of justice in order to build a sense of togetherness that round. In realizing the actualization is that various gaps must be narrowed even abolished. For example in the areas of society the students do not understand that they all have to live in a society with people around without regard to the differences that exist in the field of state while the students should understand that they all have to abide by and adhere to the government and the state. This understanding is all they get from the material presented cottage teachers. So, in essence, needed a way to print the spirit of nationalism.